2015
DOI: 10.1186/s12245-015-0077-0
|View full text |Cite
|
Sign up to set email alerts
|

Dutch senior medical students and disaster medicine: a national survey

Abstract: BackgroundMedical students have been deployed in victim care of several disasters throughout history. They are corner stones in first-line care in recent pandemic planning. Furthermore, every physician and senior medical student is expected to assist in case of disaster situations, but are they educated to do so? Being one of Europe’s densest populated countries with multiple nuclear installations, a large petrochemical industry and also at risk for terrorist attacks, The Netherlands bear some risks for incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 23 publications
(14 reference statements)
5
52
2
2
Order By: Relevance
“…Previous international studies of medical student attitudes towards hypothetical in uenza-like pandemics demonstrated a willingness (80%) 4 and a perceived ethical obligation to volunteer (77% and 70%), despite 40% of Canadian students in one study perceiving a high likelihood of becoming infected. 5,6 Amidst the current COVID-19 pandemic, our participants reported less agreement with a medical student ethical obligation to volunteer in the clinical setting at 37.8%, but believed in a higher likelihood of becoming infected at 75.6%.…”
Section: Discussionmentioning
confidence: 83%
“…Previous international studies of medical student attitudes towards hypothetical in uenza-like pandemics demonstrated a willingness (80%) 4 and a perceived ethical obligation to volunteer (77% and 70%), despite 40% of Canadian students in one study perceiving a high likelihood of becoming infected. 5,6 Amidst the current COVID-19 pandemic, our participants reported less agreement with a medical student ethical obligation to volunteer in the clinical setting at 37.8%, but believed in a higher likelihood of becoming infected at 75.6%.…”
Section: Discussionmentioning
confidence: 83%
“…20 Belgium has a limited introduction of such an educational programme in three faculties, 8 and the Netherlands has no disaster medicine programmes in their medical schools, but one faculty has expressed interest after participating in a recent national survey. 21 If these military student data are compared with those of a similar survey given to civilian senior master medical students, significantly higher score on self-estimated knowledge and capability is observed, although only 27% were senior master students; one exception regards the knowledge and capability of influenza pandemics. Results on willingness to work in various disaster scenarios are comparable between the two groups, and the results of the theoretical question/case section were significantly more favourable for the military student group.…”
Section: Discussionmentioning
confidence: 93%
“…However, the reported level of disaster knowledge was selfestimated, failing to reflect an objective relationship between medical student knowledge and willingness to respond. 12 Most nursing students report a professional obligation to volunteer in the event of a pandemic. Their WTW is even greater if adequate protection, such as PPE, is provided.…”
mentioning
confidence: 99%